Respuesta :
The general formula for an arithmetic sequence is:
a(n) = a + d(n - 1)
a : first term
d : common difference (6)
n : number of the term
In your example, you are told the 6th term is 22.
a(6) = a + 6(6 - 1) = 22
a + 30 = 22
a = 22 - 30
a = -8
So now you have the general formula:
a(n) = -8 + 6(n - 1)
If you like you can simplify it:
a(n) = -8 + 6n - 6
a(n) = 6n - 14
Then you can plug in n = 50:
a(50) = 6(50) - 14
= 300 - 14
= 286
a(n) = a + d(n - 1)
a : first term
d : common difference (6)
n : number of the term
In your example, you are told the 6th term is 22.
a(6) = a + 6(6 - 1) = 22
a + 30 = 22
a = 22 - 30
a = -8
So now you have the general formula:
a(n) = -8 + 6(n - 1)
If you like you can simplify it:
a(n) = -8 + 6n - 6
a(n) = 6n - 14
Then you can plug in n = 50:
a(50) = 6(50) - 14
= 300 - 14
= 286
assuming y ou mean aritmetic sequence since you said 'difference' as in 'common difference'
an=a1+d(n-1)
given
6th term is 22
and difference is 6
that means
a6=a1+6(6-1)=22
22=a1+6(5)
22=a1+30
minus 30 both sides
-8=a1
so we now have
an=-8+6(n-1)
find 50th term
a50=-8+6(50-1)
a50=-8+6(49)
a50=-8+294
a50=286
50th term is 286
an=a1+d(n-1)
given
6th term is 22
and difference is 6
that means
a6=a1+6(6-1)=22
22=a1+6(5)
22=a1+30
minus 30 both sides
-8=a1
so we now have
an=-8+6(n-1)
find 50th term
a50=-8+6(50-1)
a50=-8+6(49)
a50=-8+294
a50=286
50th term is 286